1989
DOI: 10.1128/aem.55.10.2561-2568.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the trpC gene from an aflatoxigenic strain of Aspergillus parasiticus

Abstract: The trpC gene in the tryptophan biosynthetic pathway was isolated from an aflatoxigenic Aspergillus parasiticus by complementation of an Escherichia coli trpC mutant lacking phosphoribosylanthranilate isomerase (PRAI) activity. The cloned gene complemented an E. coli trpC mutant deficient in indoleglycerolphosphate synthase (IGPS) activity as well as an Aspergillus nidulans mutant strain that was defective in all three enzymatic activities of the trpC gene (glutamine amidotransferase, IGPS, and PRAI), thus ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Studies of the genetics and molecular biology of A. flavus and A. parasiticus have been undertaken in an attempt to better understand aflatoxin biosynthesis (4,11,19,(23)(24)(25)28). A. flavus was chosen for our studies because of its well-described parasexual cycle and because there are 23 distinct aflatoxin pathway mutants ofA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the genetics and molecular biology of A. flavus and A. parasiticus have been undertaken in an attempt to better understand aflatoxin biosynthesis (4,11,19,(23)(24)(25)28). A. flavus was chosen for our studies because of its well-described parasexual cycle and because there are 23 distinct aflatoxin pathway mutants ofA.…”
mentioning
confidence: 99%
“…parasiticus also, but much less is known about the linkage of these genes (3). Genetic transformation systems have been developed for A. parasiticus for cloning genes in the aflatoxin biosynthetic pathway in that species (11,19,28). Feng et al (16) have also identified aflatoxin-related clones from an A. parasiticus cDNA library; the function of these clones has not been established.…”
mentioning
confidence: 99%
“…Our analyses showed that F. pedrosoi encodes all catalytic domains required for the synthesis of tryptophan; this finding opens prospects and launches new tools for a detailed and functional exploration of this essential pathway for fungal survival. Interestingly, in C. neoformans , TRP3 trpC and TRP5 trpB are essential genes [ 50 ], but the same cannot be applied to other fungi in which auxotrophic mutants were previously isolated [ 53 , 58 , 61 , 62 , 63 ]. We detected the four transcripts of the trp biosynthetic pathway ( trpB , trpC , trpD , and trpE ) by RT-PCR after WT strain biomass was incubated for 3 h in minimal medium and minimal medium supplemented with L-trp.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast trp auxotrophic mutants require low levels of exogenous tryptophan [for S. cerevisiae 20 µg/mL (0.1 mM), Hansenulla 30 µg/mL (0.15 mM) and Candida guilliermondii 40 µg/mL (0.2 mM)] [ 52 , 53 , 55 ]. On the opposite way, some filamentous fungi, as well as F. pedrosoi , demand 10 to 100 times higher amounts of this amino acid [ Aspergillus niger (1 mM), Metarhizium anisopliae (5 mM) and Nodulosporium sp (10 mM)] [ 58 , 61 , 62 , 80 ]. Eckert and colleagues suggested that the increased demand for tryptophan might be due to the limited ability to uptake the amino acid from the external source [ 63 ].…”
Section: Discussionmentioning
confidence: 99%